An assessment of the local government units' functional assignments under a decentralized regime - Marianne N. Juco; Ricxie B. Maddawin; Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2024)
The Philippines embraced a devolution agenda in 1991, leading to the enactment of the Local Government Code (LGC). Despite over three decades of implementation, devolution has remained incomplete, giving rise to the blurred accountability between the national government and local governments (LGUs), and the inefficient delivery of basic devolved services. In March 2023, President Ferdinand Marcos, Jr. ordered a review of the functions, services, and facilities that will be fully devolved to local governments. As an input to this review, the study assesses the LGU functional assignments across three critical sectors-health, infrastructure, and agriculture. The study performs an "unbundling" of the broad functions identified in the LGC and examines these in view of the principles of functional assignment and the binding constraints that have hindered devolution in the country. An expenditure analysis is employed to assess whether the increase in available financing in the first year of implementation of the Mandanas ruling has translated to an increase in service delivery of devolved functions as reflected in LGU spending. The study finds that the emphasis on subsidiarity and local autonomy coupled with the country's binding constraints and have resulted in large gaps between the de jure and de facto functional assignments, and disparities in assumed devolved functions across LGUs. The data further indicates an uneven uptake or utilization of the increase in available funding across the different levels of LGUs. The discussion points to the need for a reevaluation of the functional assignments, as well as the government strategy in addressing the binding constraints that continue to hinder devolution: fiscal imbalances, institutional capacity, enforcement, and political economy factors. Specifically, the study recommends a re-assignment of the devolved functions-between national and local, and among the different levels of local government- that not only accounts for institutional constraints but also aligns benefits and costs, and accounts for inter-jurisdictional spillovers.
Keywords: 330; decentralization; devolution; local governance; functional assignment; expenditure assignment; Mandanas ruling